Clinical outcomes and prognostic factors for gastric cancer patients with bone metastasis. Issue 1 (December 2017) - Mikami, Jota; Kimura, Yutaka; Makari, Yoichi; Fujita, Junya; Kishimoto, Tomoya; Sawada, Genta; Nakahira, Shin; Nakata, Ken; Tsujie, Masaki; Ohzato, Hiroki
Abstract Background Bone metastasis due to gastric cancer is rare, and the clinical features have not been fully evaluated. We investigated the clinical features, treatment outcomes, and prognostic factors in gastric cancer patients with bone metastasis. Methods We retrospectively collected data on 34 consecutive patients who were diagnosed radiologically with bone metastasis due to gastric cancer. We estimated the overall survival after the diagnosis of bone metastasis using the Kaplan-Meier product-limit method and evaluated which clinicopathological factors were associated with prognostic factors for survival using univariate and multivariate Cox proportional hazards regression models. Results The treatment for the primary tumor was surgery in 16 patients (47.1%) and chemotherapy in 18 patients (52.9%). The median serum alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) levels at the time of bone metastasis were 375.5 and 249 IU/L, respectively. Ten patients (29.4%) were diagnosed with bone metastasis and gastric cancer at the same time. The 6-month survival rate after the diagnosis of bone metastasis was 63.8%, and the median survival time was 227.5 days. Multivariate analysis revealed that metachronous metastasis (p  = 0.035) and extraosseous metastasis (p  = 0.028) were significant risk factors for poor survival. Conclusions The prognosis of gastric cancer with bone metastasis was poor, and metachronous metastasis and extraosseous metastasis were shown to be poor prognostic factors. Serum ALP, LDH, and tumor markers are not always high, so aggressive diagnosis using appropriate modalities such as bone scan, MRI, or PET-CT may be necessary in routine practice even in asymptomatic patients.